Dichlorido(di-2-pyridyl sulfide-κ(2) N,N′)zinc(II) - Wriedt, Mario (International Union of Crystallography, 2007)
The crystal structure of the title compound, [ZnCl(2)(C(10)H(8)N(2)S)], consists of a six-membered chelate ring in which the Zn atom is approximately tetrahedrally coordinated by two chloride ions and by the two pyridyl N atoms of a single di-2-pyridyl sulfide ligand. As usual for this type of complex, the sulfide group does not participate in zinc coordination. The dihedral angle between the two pyridine rings is 50.4 (1)°.